Proposed Marketing Strategy For CN235-220 Aircraft to Enter Latin America & Africa Region (The Indonesian Journal of Business Administration, 2021)
In the last five years PT Dirgantara Indonesia (PTDI) has experienced a decline in its military aircraft business portfolio, the problem is that PTDI is very dependent on the Ministry of Defense's strategic plans and focused to penetrate the Asia Pacific Region. On the other hand, many CN235 aircraft operating in Latin America and Africa are already aging and are likely to be replaced with PTDI products. In addition, other problems come from the marketing mix, limited marketing & sales manpower and the absence of monitoring and evaluation. To formulate the right strategy, the author uses internal analysis, namely VRIO analysis, STP (Segmenting, Targeting, and Positioning) and Marketing Mix. In addition to external analysis, the authors use CAGE distance, PESTEL analysis (Political, Economic, Sociocultural, Technological, Ecological, and Legal), Porter's 5 Forces analysis, competitor analysis, and customer analysis. From the whole analysis, the marketing strategy to enter Latin America can be started from Chile, the global strategy is to use the Global Standardization Strategy with a joint venture entry vehicle, the proposed marketing strategy, for the product starts from support excellent product support and provides maintenance and modification for the CN235 aircraft in Latin America after that PTDI can offer to sell aircraft products. For Price, PTDI can offer a financing scheme, for Place PTDI can collaborate/joint venture with local companies, for Promotion, PTDI can participate in aviation exhibitions, make marketing events with vendors, make presentations, and collaborate with the Indonesian Embassy and Athan in Latin America . For Africa, can starting from Morocco, the proposed strategy for the product is to be able to sell CN235 aircraft with the same business scheme as Senegal, serve aircraft services, develop new configurations for CN235-220 aircraft. For Price, PTDI can offer financing schemes and conduct countertrade schemes, for Place PTDI can strengthen collaboration with existing resellers and open cooperation with marketing representatives in potential countries, and build maintenance center facilities. For promotion, PTDI can participate in aviation exhibitions, roadshows to African governments, and collaborate with the Indonesian Embassy and Athan. The implication of those PTDI global strategy, the suitable organizational structure is Multidivisional structure.Keywords: Military aircraft, global standardization strategy, joint venture, marketing strategy